2016
DOI: 10.1007/s11528-016-0084-x
|View full text |Cite
|
Sign up to set email alerts
|

Graduate Students’ Readiness and Perceptions of the Pedagogical Application of Collaborative Video Logs

Abstract: Group work projects are common components of graduate course curricula. Instructors often try to mitigate the benefits of group work projects for students while avoiding negative effects. Informal learning and participatory culture practices like video logs can enhance learning environments. Video logs that promote both informal learning and participatory culture practices have captured the interest of researchers as a popular way to disclose observations, reflections and thoughts about people's lives and expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…While past studies have demonstrated the affordance of vlogs in promoting reflective thinking both among graduate students (Fox & Cayari, 2016) and ESL learners (El-Garawany, 2017), past research has also provided a few caveats to the use of vlogs as a means to learning. The first is the need to manage the affective factors of participants of vlogs, particularly in a wider audience setting, as vlogs are able to simultaneously 'make learners take greater responsibility for their work, and provoke greater anxiety' (Hung & Huang, 2015, p. 625).…”
Section: The Affordance Of Vlogs As a Medium For Reflective Practicementioning
confidence: 99%
See 1 more Smart Citation
“…While past studies have demonstrated the affordance of vlogs in promoting reflective thinking both among graduate students (Fox & Cayari, 2016) and ESL learners (El-Garawany, 2017), past research has also provided a few caveats to the use of vlogs as a means to learning. The first is the need to manage the affective factors of participants of vlogs, particularly in a wider audience setting, as vlogs are able to simultaneously 'make learners take greater responsibility for their work, and provoke greater anxiety' (Hung & Huang, 2015, p. 625).…”
Section: The Affordance Of Vlogs As a Medium For Reflective Practicementioning
confidence: 99%
“…The first is the need to manage the affective factors of participants of vlogs, particularly in a wider audience setting, as vlogs are able to simultaneously 'make learners take greater responsibility for their work, and provoke greater anxiety' (Hung & Huang, 2015, p. 625). Other than performance anxiety, there is also a need for instructors to coach participants on digital literacy, with the emphasis on the use of video recording and editing (Fox & Cayari, 2016). Danielowich (2014) calls for teacher educators to provide the relevant scaffold in the vlogs in order to better focus and direct teachers' reflection towards embracing a chance in their practice.…”
Section: The Affordance Of Vlogs As a Medium For Reflective Practicementioning
confidence: 99%
“…Por último, pese al predominio inicial de artículos centrados en el uso de YouTube para el aprendizaje dentro de los contextos formales de educación, poco a poco se abren paso nuevas producciones científicas centradas en el estudio de YouTube como medio de aprendizaje informal (Fox y Cayari, 2016;Masanet et al, 2019;Vizcaíno-Verdú et al, 2019). Gracias a ello, se abre un nuevo espacio de investigación en el campo de la educación, todavía por explorar.…”
Section: Discusión Y Conclusionesunclassified